2018
DOI: 10.2478/rjdnmd-2018-0031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fiber-Rich Snacks on C-Reactive Protein and Atherogenic Index in Type 2 Diabetes Patients

Abstract: Background and aims: High levels of non-HDL and atherogenic cholesterol can induce inflammation, and as risk factor for cardiovascular diseases. This study was to evaluate the effects of fiber-rich snacks on non-HDL cholesterol, atherogenic index, and C-reactive protein (CRP) levels in type 2 diabetes patients (T2DM). Material and Methods: Twenty T2DM patients, were recruited from the Policlinic of Endocrine, Dr. Sardjito General Hospital, Yogyakarta, Indonesia. The subjects received daily 32g fiber-rich snack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 23 publications
0
4
0
5
Order By: Relevance
“…Another study of 30 T2DM patients who consumed 21 g of MA crispy flakes per day for eight weeks also observed a weight loss, a decrease in waistline, and an increase in free fatty acids, although this was insignificant (Sunarti et al, 2014). A snack made of mixed MA and Dioscorea esculenta given to T2DM patients also reduced non-HDL cholesterol levels and the atherogenic index (Sunarti et al, 2018).…”
Section: Hypocholesterolaemic Propertymentioning
confidence: 88%
See 2 more Smart Citations
“…Another study of 30 T2DM patients who consumed 21 g of MA crispy flakes per day for eight weeks also observed a weight loss, a decrease in waistline, and an increase in free fatty acids, although this was insignificant (Sunarti et al, 2014). A snack made of mixed MA and Dioscorea esculenta given to T2DM patients also reduced non-HDL cholesterol levels and the atherogenic index (Sunarti et al, 2018).…”
Section: Hypocholesterolaemic Propertymentioning
confidence: 88%
“…Conversely, other studies reported no decrease in fasting blood glucose levels or glycated haemoglobin in DM patients who consumed a snack rich in fibre made from MA, Dioscorea esculenta, cassava, and pumpkin (as much as 32 g per day for four weeks) alongside a restricted diet of 1,500 kcal daily (Sunarti et al, 2018). This had likely been due to other foods that were not reported, and limited only for the sake of calorie intake.…”
Section: Hypoglycaemic Propertymentioning
confidence: 93%
See 1 more Smart Citation
“…Ararot bitkisinin ve rizomlarının antioksidan [5,11,13,15,16,18,41] ve anti-inflamatuvar [12,16,32,61] aktiviteleri yapılan çeşitli çalışmalarda rapor edilmiştir. Literatüre göre taze rizom ekstresinin antioksidan aktivitesi (1.78 μg/ml) taze yaprak ekstresinin antioksidan aktivitesinden (0.27 μg/ml) daha yüksektir [5].…”
Section: Antioksidan Ve Anti-inflamatuvar Etkiunclassified
“…A previous study demonstrated that nano-sized fibers extracted from sugarcane could significantly attenuate lipid deposition in the liver of HFD-fed mice by enhancing the signaling system composing hepatic fibroblast growth factor 21, AMP-activated protein kinase, and insulin ( 11 ). Finally, as illustrated in type-2 diabetes mellitus (T2DM) patients, the consumption of a high-fiber snack effectively decreases c-reactive peptide and body mass index levels ( 13 ). Whether dietary fiber of yam bean tubers also counteracts detrimental effects caused by HFD, however, remains unclear.…”
Section: Introductionmentioning
confidence: 99%